2017
DOI: 10.1186/s41182-016-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Poverty-related diseases (PRDs): unravelling complexities in disease responses in Cameroon

Abstract: BackgroundIn Cameroon, poverty-related diseases (PRDs) are a major public health concern. Research and policies addressing PRDs are based on a particular understanding of the interaction between poverty and disease, usually an association between poverty indicators and health indicators for a specific country or region. Such indicators are useful but fail to explain the nature of the linkages between poverty and disease or poverty and health. This paper presents results of a study among university students, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…However, it is interesting to see that, in the case of malaria, the most common PRD, almost 90% of respondents reported that they would use informal healthcare practices. Similar results were found in our study among students [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, it is interesting to see that, in the case of malaria, the most common PRD, almost 90% of respondents reported that they would use informal healthcare practices. Similar results were found in our study among students [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…It provides insights that help to explain why a disease like malaria is such a problem in Cameroon. In a parallel study on university students in Cameroon [ 19 ], we showed that students, with a much better educational background than the CDC workers, respond to malaria in very similar ways. Because students have to pay for official healthcare, reliance on self-medication practices and informal medication was even more prominent, especially for malaria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the health belief model, individuals’ perceptions of diseases and beneficial effects of interventions that serve to counter diseases are key determinants of people’s responses to health interventions [16]. Previous studies conducted in diverse sub-Saharan African settings found that malaria was generally perceived as a major public health problem [17]. Therefore, it could be inferred that vaccination against malaria is perceived as an important preventive measure by the sub-Saharan African population and this could explain the overall high acceptance rate noted in our review.…”
Section: Discussionmentioning
confidence: 99%